Determination of Nanogram Quantities of Emodin in Pharmaceutical Preparations and Biofluids by Luminol-Myoglobin Chemiluminescence System. Issue 2 (28th May 2012) - Zhang Zhang, Yun Yun; He He, Xili Xili; Song Song, Zhenghua Zhenghua
Abstract : Based on the quenching effect of emodin on the luminol-myoglobin (Mb) reaction, a sensitive method for the determination of nanogram level emodin by flow injection chemiluminescence (FI-CL) is presented for the first time. It was found that the CL intensity from luminol-Mb system could be inhibited in the presence of emodin, and the decrement of CL intensity was linearly proportional to the logarithm of emodin concentration in the range of 0.5–300 ng · mL − 1 ( R = 0.9956) with the detection limit of0.2 ng · mL − 1 (3 σ ). At a flow rate of2.0 mL · min − 1, a complete determination of emodin, including sampling and washing, could be accomplished in 0.5 min with the relative standard deviations (RSDs) of less than 3.5% ( n = 5). The proposed method was successfully applied to the determination of emodin in pharmaceutical preparations and human serum samples. The possible CL mechanism of luminol-Mb-emodin reaction was explained.